The effect of Glurenorm (gliquidone) on lenses and skin in experimental diabetes - YARAT, AYŞEN; AKBAY, TUĞBA (My University, 2001)
The aim of this study was to investigate the effect of administering Glurenorm (gliquidone, 10 mg/kg) on the lenses and skins of streptozotocin-induced diabetic rats. The drug was given to both diabetic and control rats daily, until the end of the experiment, at day 42. The drug was administered to one diabetic and one control group from day 0 and for the other diabetic and control groups from day 14. On day 42, cardiac blood samples, skin samples, and lenses were taken from each rat. Blood glucose (BG) was measured by the o-toluidine method. The total protein, nonenzymatic glycosylation of proteins (NEG), lipid peroxidation (LPO), and glutathione (GSH) levels in the lens and skin homogenates were determined by the Lowry, thiobarbituric acid, Ledwozwy, and Ellman methods, respectively. Laemmli SDS polyacrylamide gel electrophoresis was also carried out on the lens or skin homogenates. After 42 d, Glurenorm given to the diabetic rats produced (i) significant reductions in BG, NEG, and total protein in the lenses; (ii) significant increases in GSH levels in the lenses; (iii) and no significant results in the skin. The body weights of the drug group dropped relative to day 0, but not significantly. SDS polyacrylamide gel electrophoresis revealed no significant differences in any of the protein bands between any of the groups. In the lenses, the gains in turns of reduced NEG and increased GSH may have been offset by the reduction in protein.
Keywords: Female; Animals; Skin; Glycosylation; Rats; Disease Models, Animal; Glutathione; Lipid Peroxidation; Hypoglycemic Agents; Lens, Crystalline; Blood Glucose; Diabetes Mellitus, Experimental; Streptozocin; Sulfonylurea Compounds